2016
DOI: 10.1089/thy.2016.0016
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Novel Gene Variants Associated with Congenital Hypothyroidism in a Finnish Patient Cohort

Abstract: Background: Congenital hypothyroidism (CH) is defined as the lack of thyroid hormones at birth. Mutations in at least 15 different genes have been associated with this disease. While up to 20% of CH cases are hereditary, the majority of cases are sporadic with unknown etiology. Apart from a monogenic pattern of inheritance, multigenic mechanisms have been suggested to play a role in CH. The genetics of CH has not been studied in Finland so far. Therefore, multigenic sequencing of CH candidate genes was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 39 publications
4
48
0
2
Order By: Relevance
“…The sequencing panel was designed to include all genes suggested to be associated with non-syndromic cardiomyopathies at the time of the study onset. Sequencing methods applied in this study have been previously reported, 11 and the details are presented in the Supporting Information. All pathogenic (P)/likely pathogenic (LP) variants were confirmed by Sanger sequencing.…”
Section: Genetic Analyses Of the Finhcm Genetic Studymentioning
confidence: 99%
“…The sequencing panel was designed to include all genes suggested to be associated with non-syndromic cardiomyopathies at the time of the study onset. Sequencing methods applied in this study have been previously reported, 11 and the details are presented in the Supporting Information. All pathogenic (P)/likely pathogenic (LP) variants were confirmed by Sanger sequencing.…”
Section: Genetic Analyses Of the Finhcm Genetic Studymentioning
confidence: 99%
“…The presence of RTSH-associated PAX8 promoter variants [6971], the observation of a frameshift mutation with demonstrated protein instability [72], and the autoregulation of PAX8 by binding to its own promoter [73] are also consistent with a haploinsufficiency mechanism. A noteworthy mutational hotspot is the CpG dinucleotide at codon 31, for which frequent mutational events (R31H and R31C) have been reported [61, 65, 67, 7477]. For some of the reported mutations, the primary defect is the impaired synergism with other thyroid transcription factors (NKX2-1) or insufficient recruitment of coactivators (p300) without altering DNA binding [7880].…”
Section: Rtsh Due To Loss-of-function Mutations In Pax8mentioning
confidence: 99%
“…Thus, there is no clear correlation between the activity of mutant PAX8 proteins in vitro and the severity of RTSH in patients. In addition, incomplete penetrance [83], parental mosaicism [84], and late-onset of RTSH phenotype due to insufficient postnatal thyroid growth [64, 77, 85, 86] have been shown to potentially mask the inherited nature of the condition.…”
Section: Rtsh Due To Loss-of-function Mutations In Pax8mentioning
confidence: 99%
See 2 more Smart Citations